Critical Evaluation of Audit Delay Survey in Various Manufacturing Industry 2016 - 2020 - Nungki Yartono; Asyari; Padri Achyarsyah (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
Delays in the presentation of audited financial reports will impact market reactions, especially among investors in the capital market. The effect that late reporting has on the collapse of shareholder confidence in large corporations also has profound financial implications for investors. Several factors are assumed to affect audit delay. Firm size, audit firm size, profitability, solvency, and public ownership. This study examines the effect of audit committees, liquidity, and profitability on audit delay. This research was conducted at Multi-Industry Sector Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2016-2020 period. A sampling of this study using the purposive sampling method. This research was conducted on 23 companies. The data analysis technique used is multiple linear regression analysis. Hypothesis test and coefficient test.  The results of hypothesis testing found that the Audit Committee does not affect audit delay, Liquidity has a positive effect on audit delay, and profitability has a negative effect on audit delay.